2018
DOI: 10.1021/acs.chemmater.8b02279
|View full text |Cite
|
Sign up to set email alerts
|

Mid-wave and Long-Wave Infrared Linear Dichroism in a Hexagonal Perovskite Chalcogenide

Abstract: Mid-wave infrared (IR) and long-wave IR spectral ranges are of growing interest in various applications such as thermal imaging, thermography-based remote sensing, and night vision. Materials widely used for IR photodetectors in this regime include cadmium mercury telluride alloys and nanostructures of compound semiconductor. The materials development for IR optics will drive down the cost of IR optical systems and enable larger scale deployment. Here, we report a mid-wave IR responsive material composed of ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Crystal structure of BaTiS 3 . We synthesized needle-like single crystals of BaTiS 3 with dimensions up to~2 cm × 100 μm × 50 μm using chemical vapor transport 35,36 . BaTiS 3 has a BaNiO3type hexagonal perovskite structure in which the octahedra of Ti coordinated by S atoms share common faces, resulting in chain-like structures along the c axis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structure of BaTiS 3 . We synthesized needle-like single crystals of BaTiS 3 with dimensions up to~2 cm × 100 μm × 50 μm using chemical vapor transport 35,36 . BaTiS 3 has a BaNiO3type hexagonal perovskite structure in which the octahedra of Ti coordinated by S atoms share common faces, resulting in chain-like structures along the c axis.…”
Section: Resultsmentioning
confidence: 99%
“…Growth of BaTiS 3 single crystals. Single-crystal needles were grown using chemical vapor transport, similar to methods employed for other perovskite sulfides reported elsewhere 35,36 . The precursors, barium sulfide (Sigma-Aldrich, 99.9%), titanium (Alfa Aesar, 99.9%), and sulfur (Alfa Aesar, 99.999%) were mixed stoichiometrically and loaded in a quartz ampoule with the transporting agent iodine (Alfa Aesar 99.99%) in an argon-filled glove box.…”
Section: Methodsmentioning
confidence: 99%
“…BaTiS3 belongs to an emerging family of inorganic perovskite materials with a general chemical formula, ABX3, where A is typically an alkaline earth or alkali metal ion, and B is a transition metal ion surrounded by six anions (X). [30][31][32][33] . The A ions are encapsulated within the hexagonal BX6 structure.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we have demonstrated high quality synthesis of polycrystalline TMPCs through solid state reaction in sealed ampoules, 9 as well as single crystal growth with chemical vapor transport and salt flux methods. [19][20][21] We have also evaluated their physical properties for photovoltaics and anisotropic Infrared photonic materials. 9,[19][20][21] In this work, we will study the thermal stability of several transition metal perovskite related sulfides in air, including a-SrZrS 3 (α-SZS), b-SrZrS 3 (b -SZS), BaZrS 3 (BZS), Ba 2 ZrS 4 (BZS214), and Ba 3 Zr 2 S 7 (BZS327).…”
Section: Introductionmentioning
confidence: 99%